EVALUATION OF INTEGRATIVE PERIODONTAL, SURGICAL, ORTHODONTIC AND PROSTHETIC TREATMENT IN SEVERE GENERALIZED AGGRESSIVE PERIODONTITIS - Catalina Danila; Silvia Teslaru; Vlad Danila; Ioana Rudnic; Nicoleta Ioanid; Cosmin Popa; Silvia Martu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study Evaluation and improving of periodontal status through alignment of the molars in mesial tipping. Material and methods We studied 26 patients, affected by aggresive periodontitis, with age between 26-35 years old, with extracted 3.6 and 4.6 from different reasons and second molar rotated and mesialized. Periodontal clinical exam revealed thin gingival tissue of 3-4 mm (21 cases, 80, 7%) on the mesial surface of the second molar. Radiographic exam revealed the enlargement of the periodontal space and the resorbtion of the interproximal mesial bone. The treatment for the second molar consisted in fixed orthodontic devices and different uprighting techniques depending on the periodontal status of the patient: 50% with uprighting spring, 30% with orthodontic implant and 20% with tip back technique. Results After treatment it was noticed an improving of the gingival tissue status, the reduction of the periodontal pockets with 2 mm and the reshaping of the bone. Conclusions Orthodontic treatment applied to partial toothless aims to create optimal conditions for the insertion of oral implants to represent elements of support for future prosthetic reconstruction.